On the Use of New Blockchain-based Technologies for Securely Distributing Data - Alves, Gustavo; Cavalcante, Everton; Batista, Thais (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2018: Anais do XVIII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2018.4273, 2018)
Blockchain is a distributed encrypted database that maintains a continuously growing set of data records. Aside its increasing popularity, blockchain presents some technical challenges that encourage the development of new technologies attempting to overcome them. Nonetheless, the literature still lacks more research and details about such technologies and which improvements they bring to overcome current challenges of Blockchain. This work aims at providing an overview on Blockchain, its technical challenges, and the new improving technologies.